Observing evidence of insider trading in the Athens Stock Exchange - Eleftherios Thalassinos; Dimitrios Maditinos; Athanasios Paschalidis (Journal of Economic Structures, 2012)
This study proposes a process for observing evidence of insider trading in the Athens Stock Exchange (ASE). This is performed by building an environment which, based upon previous research, common sense and information technology, may be used for observing such evidence. It is designed to be parametrically used for each stock in the sample, perform event study analysis and indicate abnormal performance that might be attributed to insider trading. To some extent, it applies knowledge discovery to retrieve meaningful information from the existing data. In this case, to identify transaction dates that might be associated with certain events. The validity of this process is assessed by relating the identified events to published announcements.
Keywords: G02; G12; G14; G15; 330